Perceived Stress During COVID-19 Pandemic: The Malaysian Nurses Experience - Pasi, Hafizah; Kamaruzaman, Nor Azam; Nasreen, Hashima E (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Research shows that nurses are one of the most vulnerable categories of professionals to develop stress and other problems due to the nature of their job. Thus the objective of this study is to describe the perceived stress experienced during the COVID-19 pandemic among Malaysian nurses. A cross-sectional study was conducted through an online form involving 319 randomly selected nurses from a teaching hospital on the east coast of Pahang, Malaysia, between January to December 2022. The perceived stress was measured using the Malay version 10-item Perceived Stress Scale, PSS-10 questionnaire. Descriptive and linear regression analysis was applied to measure the mean score of perceived stress and the association between perceived stress scores and other factors in this population. The study found that the total mean score of PSS-10 among the respondents was 19.1 ± 5.8. The three items with the highest mean scores were under the subscales “lack of self-efficiency” of the questionnaire (item-4, item-7, and item 5), while the item with the lowest mean scores belonged to subscales “perceived helplessness” (item-10). However, further analysis performed shows no significant association between perceived stress towards COVID-19 with sociodemographic and work-related factors among respondents. This study concluded that lack of self-efficiency was perceived as the main stress experienced by Malaysian nurses during the COVID-19 pandemic. Thus, it is pivotal that the nurse’s manager and higher authority of the organization focus on improving the efficiency of these nurses through targeted programs focusing on problem-solving, emotional and on-the -job management plan, along with accessibility to resources, a positive work environment and support.